Dehydration, temperature, and light tolerance in members of the aeroterrestrial green algal genus Interfilum (Streptophyta) from biogeographically different temperate soils. Issue 5 (31st July 2014) - Karsten, Ulf; Herburger, Klaus; Holzinger, Andreas; Bassi, R.
<x xml:space="preserve">Abstract</x> Unicellular green algae of the genus Interfilum (Klebsormidiales, Streptophyta) are typical components of biological soil crusts. Four different aeroterrestrial Interfilum strains that have previously been molecular‐taxonomically characterized and isolated from temperate soils in Belgium, Czech Republic, New Zealand, and Ukraine were investigated. Photosynthetic performance was evaluated under different controlled abiotic conditions, including dehydration, as well as under a light and temperature gradient. For standardized desiccation experiments, a new methodological approach with silica gel filled polystyrol boxes and effective quantum yield measurements from the outside were successfully applied. All Interfilum isolates showed a decrease and inhibition of the effective quantum yield under this treatment, however with different kinetics. While the single cell strains exhibited relatively fast inhibition, the cell packet forming isolates dried slower. Most strains fully recovered effective quantum yield after rehydration. All Interfilum isolates exhibited optimum photosynthesis at low photon fluence rates, but with no indication of photoinhibition under high light conditions suggesting flexible acclimation mechanisms of the photosynthetic machinery. Photosynthesis under lower temperatures was generally more active than respiration, while the opposite was true for higher temperatures. The presented data provide an explanation for the regular occurrence of Interfilum species in soil habitats where environmental factors can be particularly harsh.